2021
DOI: 10.3389/fpsyt.2021.751411
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Depressive Symptoms and Insomnia in College Students in Qinghai Province: The Mediating Effect of Rumination

Abstract: Background: This study investigates the mediating effect of rumination on the associations between depressive symptoms and insomnia.Methods: This is a cross-sectional study. Insomnia Severity Index (ISI), Ruminant Response Scale (RRS) and Beck Depression Inventory (BDI) were determined in 12,178 college students in Qinghai province by a questionnaire network platform.Results: The prevalence of insomnia was 38.6% in the participants. Insomnia symptoms [interquartile range: 6 (3, 9)], depressive symptoms [interq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The −2 log likelihood ratio (−2 LLR) test was used to determine whether the mediating effect improved the goodness-of-fit of the model ( 41 ). The −2 LLR decreases by 3.84 or more (Chi-square limit of 1 degree of freedom is 0.05), indicating that one model is superior to the other.…”
Section: Methodsmentioning
confidence: 99%
“…The −2 log likelihood ratio (−2 LLR) test was used to determine whether the mediating effect improved the goodness-of-fit of the model ( 41 ). The −2 LLR decreases by 3.84 or more (Chi-square limit of 1 degree of freedom is 0.05), indicating that one model is superior to the other.…”
Section: Methodsmentioning
confidence: 99%
“…Two disorders that commonly occur along with insomnia disorder are anxiety and depression. A prospective study on the general population found that insomnia was closely linked with depression and anxiety (Jansson-Fröjmark and Lindblom, 2008), the result that was replicated in a large body of evidence (e.g., Baglioni et al, 2011;Blake et al, 2018;Hertenstein et al, 2019;Morin et al, 2021;Xiao et al, 2021). As such, the effect of sociodemographic characteristics on insomnia severity has been documented in various studies.…”
Section: Introductionmentioning
confidence: 91%
“…Two disorders that commonly occur along with insomnia disorder are anxiety and depression. A prospective study on the general population found that insomnia was closely linked with depression and anxiety (4), the result that was replicated in a large body of evidence [e.g., (5)(6)(7)(8)(9)]. As such, the effect of sociodemographic characteristics on insomnia severity has been documented in various studies.…”
Section: Introductionmentioning
confidence: 98%